Spatial distribution of tenebrionid beetles in relation to environmental variability in Península Valdés, Patagonia - Cheli, German Horacio (2018)
Deserts provide atmospheric-climatic regulation and other several important ecosystem services that many human activities, through habitat degradation and species lost, could severely impact. A sustainable management of arid ecosystems is needed to prevent these undesirable consequences, and knowledge of biodiversity spatial patterns as well as understanding of their spatial distribution in relation to environmental and climatic factors are essential for this. The Natural Protected Area Península Valdés (PV) exhibits an important environmental variation which allows it to host a considerable biodiversity. Recently the knowledge of the terrestrial arthropods in PV have greatly increased, showing that tenebrionid beetles (Coleoptera: Tenebrionidae) are among the most abundant groups and species diverse insect. At the same time, it is known that these beetles are important for the functioning of desert ecosystems (eg. litter fragmentation processes and soil biogeochemical cycles). In this work we study for the first time the spatial distribution of darkling beetles in relation to environmental variability in PV, identifying the most important species assemblages and the main environmental variables that determine them. Tenebrionid species records were compiled from own entomological collection trips, bibliography and from revision of national entomological collections. Habitat information was collected from bibliography and satellite images. Multivariate statistics evidenced that environmental variability within PV determines different assemblages of tenebrionid species into the region. Most important species that differentiate these assemblages were Nyctelia picipes, Epipedonota cristallisata, Blaptinus punctulatus, Mitragenius araneiformis and Emmallodera hirtipes. Main environmental determinants of their distributions were temperature, rainfall, slope, soil type, geomorphology and percentage of vegetation cover. Our findings contribute to the sustainable use of arid Patagonia and improve both future environmental classifications and predictions of biodiversity changes into the region.